Respostas
respondido por:
27
(I)
x + y = 10
(II)
x - y = 4
Adição:
x + y + x - y = 10 + 4
2x = 14
x = 14/2
x = 7
x + y = 10
7 + y = 10
y = 10 - 7
y = 3
Solução:
x = 7
y = 3
x + y = 10
(II)
x - y = 4
Adição:
x + y + x - y = 10 + 4
2x = 14
x = 14/2
x = 7
x + y = 10
7 + y = 10
y = 10 - 7
y = 3
Solução:
x = 7
y = 3
respondido por:
10
x + y = 10
x - y = 4
----------------
2x = 14
x = 14/2
x = 7
x + y = 10
7 + y = 10
y = 10 - 7
y = 3
x - y = 4
----------------
2x = 14
x = 14/2
x = 7
x + y = 10
7 + y = 10
y = 10 - 7
y = 3
Perguntas similares
7 anos atrás
9 anos atrás
9 anos atrás
9 anos atrás
9 anos atrás
9 anos atrás
9 anos atrás